Hidrólise enzimática de fígado suíno e caracterização de potenciais bioatividades formadas - Maluf, José Uebi (2020)
The high volume of industrial waste generated by the meat products industry has driven a new market niche, that of protein hydrolysates. Since these co-products are an opportunity to explore raw materials of low commercial value, however, rich in proteins of high biological value, vitamins and minerals. In this context, the present work aimed, through enzymatic hydrolysis of swine liver, from slaughter, to obtain protein hydrolyzate, which can form bioactive compounds with nutritional and functional properties to be incorporated into human and animal feed, adding value to animals. by-products of pig slaughter, and still collaborating for a clean and sustainable technology. In order to establish the functional properties and composition of the raw material, pig liver, it was determined the chemical composition, vitamins, minerals and amino acid profile, in order to verify its application potential. After this stage, enzymatic hydrolysis tests were carried out using two enzymes, Alcalase 2.4 L® and NovoPro-D®, following the experimental design of the DCCR type with 4 axial points. At the end, tests were carried out to make the process feasible. Therefore, for the best test, hydrolysis kinetics were performed. In all plans, the independent variables evaluated were: enzyme: substrate ratio and protein: water ratio, the dependent variable was the degree of hydrolysis (GH) of the proteins. The results revealed that the pig liver has excellent nutritional quality, with high protein content (19.73%) and low fat (2.4%), moisture (74.3%) and ash (1.4%) , balanced presence of all essential amino acids (50.05% EAA), vitamins A, B complex and minerals, all detected in sufficient quantities to supply the body's daily needs. After analyzing the conditions that presented the best results, in terms of hydrolysis, considering the restrictions to be applied on a large scale, for the enzymes Alcalase 2.4 L® and NovoPro-D® it was established as temperature (64 ° C), enzyme ratio: substrate (1.5% and 3.0%) and protein: water with (20% and 22%), respectively, for a period of 1 hour with a pH around (6.0-6.5), for each enzyme. The hydrolysates from the Alcalase 2.4 L® and NovoPro-D® reactions resulted in hydrolysis degree values of 27.86% and 27.30% respectively. Studies have shown that hydrolysates are rich sources of necessary nutrients such as proteins, essential amino acids, minerals and vitamins. Electrophoresis confirmed that there was hydrolysis in all samples, with the formation of peptides with low molecular mass, with bands below (14kDa), in addition, it was detected that the protein hydrolyzate has functional properties, increasing the application possibilities, the functionalities being water and oil absorption capacity, emulsifying capacity and stability, and foaming capacity and stability. In view of these results, it was possible to show that the pig liver is an excellent raw material, rich in proteins of high biological value with potential that can be transformed into protein hydrolyzate through an enzymatic process. Enzymatic hydrolysis, under the conditions of the study evaluated, showed antioxidant, anti-diabetic and anti-hypertensive capacity, increasing with the hydrolysis time. Due to the formation of these bioactive molecules this new product is able to improve the nutritional and biological properties, in order to be incorporated into human and animal food.